Risk Prediction of Appendicitis Perforation in Children Based on Leukocyte ond Neutrophil Count: A Logistic Regression Analysis - Hafni Zuchra Noor; Imaniar Ranti; Akhmad Makhmudi (International Journal Labs, 2026)
Appendicitis in children is an emergency condition with a high risk of perforation, so it requires correct diagnosis and immediate treatment to prevent complications. Although leukocyte and neutrophil values ??are often used as initial indicators in diagnosing appendicitis, there is no clear consensus regarding the correct prediction of the risk of perforation in appendicitis. This study aims to predict the risk of perforation based on leukocyte and neutrophil values ??through logistic regression analysis. This retrospective study used secondary data from 195 pediatric patients diagnosed with appendicitis who were treated at the PKU Muhammadiyah Gamping Hospital. The results of logistic regression analysis showed that neutrophils significantly increased the risk of perforated appendicitis (OR = 1.040; 95% CI: 1.011-1.070; p = 0.006), while leukocyte values did not show a significant effect (OR = 1.031; 95% CI: 0.987 – 1.078; p = 0.172) with moderate model predictive ability (Nagelkerke R2 = 0.108). This study concluded that neutrophils are a more sensitive laboratory indicator than leukocyte values ??for predicting the risk of perforated appendicitis in children.